1999
DOI: 10.1128/iai.67.5.2522-2530.1999
|View full text |Cite
|
Sign up to set email alerts
|

Towards aTaenia soliumCysticercosis Vaccine: an Epitope Shared byTaenia crassicepsandTaenia soliumProtects Mice against Experimental Cysticercosis

Abstract: The Taenia crassiceps recombinant antigen KETc7 has been shown to be effective as a vaccine against experimental murine cysticercosis, a laboratory model used to test potentially promising molecules against porcine Taenia soliumcysticercosis. Based on the deduced amino acid sequence of this proline-rich polypeptide, three fragments, GK-1, GK-2, and GK-3, were chemically synthesized in linear form. Of the three peptides, only GK-1 induced sterile protection against T. crassicepscysticercosis in 40 to 70% of BAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(28 citation statements)
references
References 23 publications
0
19
1
8
Order By: Relevance
“…Cell proliferation was evaluated using standard flow cytometry protocols [43,44]. After 5 days cells were harvested and stained with Phycoerythrin Cyanin 5.1 (PE-Cy™ 5)-conjugated anti-CD3 (BD Biosciences, USA, cat.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…Cell proliferation was evaluated using standard flow cytometry protocols [43,44]. After 5 days cells were harvested and stained with Phycoerythrin Cyanin 5.1 (PE-Cy™ 5)-conjugated anti-CD3 (BD Biosciences, USA, cat.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…In addition, GK1 is known to stimulate the production of the proinflammatory cytokines IFN-c and TNF-a and the inflammatory chemokine CCL2 (MCP-1) in dose-dependent manners. 25 These effects of GK1, along with other unexplored innate and adaptive immune mechanisms, could at least, in part, explain the observed anti-tumoral effects of this peptide in an experimental murine model of melanoma. Thus, it is feasible to speculate that IFN-c could play a central role in the antitumor effects observed in this study, as IFN-c has been shown to be a mediator of tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…This therapeutic effect could have been related to various immune mechanisms stimulated by GK1, 27 but its precise role as an anti-tumoral molecule remains to be determined. Since GK1 exerts its effects in a dose-dependent manner, and it is rapidly cleared from the body, 25 it has the potential to be used as a primary or adjuvant component of chemotherapeutic cocktails to treat experimental and human cancers. Currently, our group is performing studies to determine whether GK1 induces the same proinflammatory cytokine profiles in mouse melanoma models and whether these effects are dose dependent.…”
Section: Gk1 Increases Survival In Murine Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…Several efforts have been attempted to obtain an effective vaccine against cysticercosis. The designs include total protein extracts, partially purified excretion antigens, vaccine peptide synthesis and DNA vaccines (2)(3)(4)(5)(11)(12)(13). But discrepancies regarding the more appropriate antigen type for inducing effective immunity still exist (4,12).…”
Section: Discussionmentioning
confidence: 99%